Efforts to Improve the Quality of Schools Based on the Analysis of Educational Reports - Sundakir Sundakir; Makhdalena Makhdalena; Hambali Hambali (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this study was to examine school quality report cards in order to enhance the standard of education. This study employs descriptive qualitative methodologies, which involve analysing data or documentation, doing observations, and conducting interviews. Data collecting methods encompassed interviews, observation, and documentation. The participants in this study included the principal, vice principal, school treasurer, three teachers, and five studentss, who provided information. In addition, the employed data analysis technique is comprised of data reduction, data collecting, data display, and conclusion. The findings of this study suggest that the implementation of school report cards or education report cards can enhance the overall quality of schools. The indicators on the quality report card that can enhance the quality of school education include the quality and pertinence of student learning outcomes, which are categorised as satisfactory and progressing in relation to students' reading skills, numeracy abilities, and character dimensions. Consequently, there is a positive correlation between pupils' proficiency in literacy and the overall quality of education, including numeracy and character development. The school's quality is directly proportional to the pupils' level of numeracy skills and character. Schools must consistently aim for high-quality student learning outcomes, necessitating changes in all areas that contribute to student achievement.